Chitosan Nanoparticles for Topical Drug Delivery in Chemotherapy-Induced Alopecia: A Comparative Study of Five Repurposed Pharmacological Agents - Salma A. Fereig; John Youshia; Ghada M. El-Zaafarany; Mona G. Arafa; Mona M. A. Abdel-Mottaleb (Pharmaceuticals, 2025)
Background/Objectives: Chemotherapy-induced alopecia is a common and distressing side effect of cancer treatment, significantly impacting patients’ psychological well-being. Nanocarriers offer a promising strategy for targeted drug delivery to hair follicles, while chitosan nanoparticles have demonstrated hair-growth-promoting properties. This study explores the potential of chitosan nanoparticles as a topical delivery system for five pharmacological agents—phenobarbital, pioglitazone, rifampicin, N-acetylcysteine, and tacrolimus—to prevent chemotherapy-induced alopecia. Methods: Drug-loaded chitosan nanoparticles were prepared using the ionic gelation technique and characterized by particle size, zeta potential, entrapment efficiency, FT-IR spectroscopy, and TEM imaging. Their efficacy was assessed in a cyclophosphamide-induced alopecia model in C57BL/6 mice through macroscopic observation, histopathological examination, and scanning electron microscopy of regrown hair. Results: The prepared particles were spherical, cationic, and between 205 and 536 nm in size. The entrapment efficiencies ranged from 8% to 63%. All five drugs mitigated follicular dystrophy, shifting the hair follicle response from dystrophic catagen to dystrophic anagen. Phenobarbital demonstrated the most significant hair regrowth and quality improvements, followed by N-acetyl cysteine and pioglitazone. Tacrolimus showed moderate efficacy, while rifampicin was the least effective. Conclusions: These findings suggest that phenobarbital-loaded chitosan nanoparticles represent a promising approach for the prevention and treatment of chemotherapy-induced alopecia, warranting further investigation for clinical applications.